(untitled) (Innovative professional education, 2024)
The summarizes the scientific achievements of fundamental research on the role of legal competence of vocational teachers of vocational education institutions in the construction industry. The essence of the environmental component of legal competence as the ability to understand and manage environmental processes is substantiated. The regulatory documents in the environmental sphere that are mandatory for use in the construction industry are summarized. Regulatory requirements and legal aspects are characterized, and the need to train future professionals with environmental awareness is proved.